Building the system of product quality control tools for vietnamese garment enterprises - Tran, Dai Nguyen; Ho , Thi Minh Huong (Journal of Technical Education Science, 2019)
For the manufacturing industry, quality control is a critical step to ensure customers receive products free from defects. When the process is done in the wrong way, it will put both consumers and corporation at great risk. Therefore, we proudly introduce the following model: “Quality Management System”, which is specifically designed for the garment industry. Our model was applied successfully for the production of Wash Denim at Phong Phu International (PPJ), one of the leading garment-textile manufacturers and exporters in Vietnam.